The use of electrothermophototherapy in patients with temporomandibular disorders (Research, Society and Development, 2022)
The temporomandibular joint (TMJ) is one of the most complex joints in the human body, its biomechanics essential and essential, and its functions are extremely important for human daily activities, swallowing, speaking, breathing, chewing, among others. Unfortunately, currently, disorders in this articulation have affected a large population, not limited to age groups. The evolution of physiotherapy has been shown to be more and more evident and constant is of paramount importance in the treatment of these disorders, enabling not only the conventional treatment protocol, but electrothermophototherapeutic resources that help in the search for symptom relief. The aim of this research was to verify the use of electrothermophototherapy in patients with temporomandibular disorders. This is a literary review carried out in the Scielo Lilacs and Pubmed databases. Studies have shown that the use of resources is beneficial and effective. It is concluded that the resources used in line with conventional treatment provide improvements in symptom relief, but there is still a shortage of literature and studies on the subject.